Understanding social justice leadership: An international exploration of the perspectives of two school leaders in Costa Rica and England - Torres, Nancy (2014)
This article is an examination of two social justice leaders, one in Costa Rica and one in England. It is part of the International Study of Leadership Development Network, a multi-nation study of social justice and educational leadership. A brief discussion of the philosophy of social justice and an examination of the macro and micro context in each of the countries set the stage to understand the social perspective of the two school leaders. Interviews were conducted to construct a narrative to illuminate their views of social justice. A comparison of the leaders found more similarities than differences even though the settings in each country were quite different. They both felt that it was important to challenge inequities in society and demand that the government provide for all citizens; they emphasized respect for students; and, to some extent, they grounded their beliefs in faith. These narratives can be valuable for both practitioners and researchers to learn from the conceptions of social justice and the challenges of these leaders. Illuminating the agency of a school leader in one national context may stir the possibility of emancipation in another context.